Chemical constituents and anti-inflammatory effects of some stilbenoids from Dipterocarpus retusus fruits of Vietnam - Hung, Ho Dac; Tien, Doan Duy; Ngoan, Nguyen Thi; Duong, Ba Thi; Viet, Do Quoc; Dien, Pham Gia; Anh, Bui Kim; Nghi, Do Huu (Vietnam Journal of Science and Technology, 2021)
In this work, the crude MeOH extract of fruits of Dipterocarpus retusus Blume (Dipterocarpaceae) growing in Vietnam was prepared and studied. Five compounds: ε-viniferin, paucifloroside, ursolic acid, quercetin, and (+)-catechin, was isolated. The structures of these compounds were elucidated by spectroscopic methods. The extracts from fruits of D. retusus Blume by metanol and its some isolated stilbene compounds were evaluated for anti-inflammatory effect activities.